Analysis of emerging organic contaminants in poultry manure by gas chromatography–tandem mass spectrometry. Issue 4 (27th December 2017) - Aznar, Ramón; Albero, Beatriz; Pérez, Rosa Ana; Sánchez‐Brunete, Consuelo; Miguel, Esther; Tadeo, José L.
Abstract: A multiresidue method was developed for the determination of 19 emerging organic contaminants (pharmaceutical drugs, personal care products, and bisphenol A) in poultry manure. Lyophilized samples of manure were extracted by ultrasound‐assisted matrix solid‐phase dispersion and the extracts were analyzed by gas chromatography with tandem mass spectrometry after derivatization. Analysis of spiked poultry manure samples, at levels ranging from 25 to 150 ng/g, gave satisfactory recovery results for all the compounds, with values from 67 to 106%. The developed procedure provided detection limits that ranged from 0.9 to 2.2 ng/g. Finally, the validated method was applied to poultry manure samples collected from 23 poultry farms in Spain. Salicylic acid was found in most of the samples analyzed at levels up to 2501 ng/g, whereas, methyl paraben, orthophenylphenol, ibuprofen, paracetamol, and carbamazepine were detected at levels up to 250 ng/g. Composting of manure showed an important decrease in the levels of the detected contaminants.